Increasing lysergic acid levels for ergot alkaloid biosynthesis: Directing catalysis via the F-G loop of Clavine oxidases - Lim, Li Rong; Wong, Garrett; Go, Maybelle K.; Yew, Wen Shan (Frontiers in Microbiology, 2023)
Most ergot alkaloid drugs are semi-synthetically derived from the natural product lysergic acid, a valuable precursor for the development of novel ergot alkaloid drugs. Clavine oxidase (CloA) is a putative cytochrome P450, identified in the ergot alkaloid biosynthesis pathway, and a key enzyme that catalyses the formation of lysergic acid from the precursor alkaloid agroclavine in a two-step oxidation reaction. We demonstrated in this study that Saccharomyces cerevisiae can be used as a viable host for the functional expression of CloA from Claviceps purpurea and its orthologues. We also showed that CloA orthologues differ in their ability to oxidise the substrate agroclavine, with some orthologues only able to perform the first oxidation reaction to produce elymoclavine. Of particular note, we identified a region between the F-G helices of the enzyme that may be involved in directing oxidation of agroclavine by substrate recognition and uptake. Using this knowledge, engineered CloAs were shown to produce lysergic acid at levels exceeding that of wildtype CloA orthologues; a CloA variant, chimeric AT5 9Hypo CloA, increased production levels of lysergic acid to 15 times higher as compared to the wildtype enzyme, demonstrating future utility for the industrial production of ergot alkaloids using biosynthetic routes.